Evaluasi Karakter Morfo-fisiologis Sumber Daya Genetik Padi Berumur Genjah - Setyowati, Mamik; Hidayatun, Nurul; Sutoro, Sutoro; Kurniawan, Hakim (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2014)
Rice varieties with short maturity and high productivity can be achieved when there is available genetic resources in a sufficient level of variability. Morphological characters, such as leaf thickness and crop growth rate, could affect in crop productivity. Evaluation of seed germination rate, crop growth rate,Â  and their efficiency used for nitrogen have been done on 25 accessions of rice. Seed germination rate of B11283-6C-PN-5-MR-34-1-1-3, Lariang, B11742-RS-2-3-MR-34-1-2-3 reached 1,0-1,3 g/hill/day during seed initiation, while Dodokan and Silugonggo reached 0.7-0.8 g/hill/day. Danau Atas, B.11283-6C-PN-5-MR-2-3-Sl-1-2-1-1, B11742-RS-2-3-MR-34-1-2-3 and B11742-RS-2-3-MR-34-1-4-1 lines show good perfomance, moreover B11742-RS-2-3-MR-34-1-1-3, B11742-RS-2-3-MR-34-1-1-4 and B11742-RS-2-3-MR-34-1-1-4 lines produced grain yield higher than Silugonggo and Dodokan varieties. Those lines could be harvested at about 96 days after planting.